How to teach your children to pack their backpacks for travel? An easy guide - Harun, Nur Syikri; Ismail, Fathiyah (Fakulti Pengurusan Perniagaan, UiTM Terengganu, 2022)
Having children travelling with you may pose some other challenges. For parents who need to pack their children's luggage, it would be tiring if they do it all alone. Asking for your children's helping hand would be great; however, you need to pay attention to what's being packed by your children. This is because some important stuffs may be overlooked of left unnoticed by your children. Say, if they're about to take part in sports or other events that require them to cover or protect their feet, forgetting to bring along sports shoes and pairs of socks would spell a disaster, which wouldn't be an option.